Cumplimiento de los indicadores de calidad en el área de centro quirúrgico del Hospital General Manuel Ygnacio Monteros – Loja - Salinas Minga, Juan Andrés (2023)
The quality of attention can be defined as those services that are provided in the best scientific, professional, and institutional conditions, in an accessible and equitable way to satisfy and adhere to the user. For this reason, for all health professionals, offering care based on safety and quality has been transformed on their greatest ideal. The present research was aimed at evaluating, through documentary and observational review, the compliance with quality indicators by the surgical center service of the Manuel Ygnacio Monteros General Hospital, with respect to safe administrative, assistance and administrative/assistance practices. It was a non-experimental, descriptive, cross-sectional research. The instrument used for data collection was an observation form, which was prepared based on the checklist and formats established in the MSP patient-user safety manual. The results were interpreted in tables, which were created using the Microsoft Excel program. The results showed that the surgical center service is staffed by 17 nursing professionals and 11 auxiliary nurses, in addition to 6 operating rooms, 2 dressing rooms and 3 warehouses. In relation to the administrative and assistance practices, it was found that there was 100% compliance; while, regarding the administrative/assistance practices, compliance was 88.52%, with the correct handling of infusion pumps and patient safety education being 100%, while safe surgical practices were the least complied with (77.78%).